Institutional factors and subnational location choice for multinationals' R&D subsidiaries - Christian Falaster; Manuel Portugal Ferreira (Innovation & Management Review, 2020)
Purpose - Using an institution-based view, this study aims to conceptualize how sub-national institutional characteristics are likely to explain location choice of multinationals' research and development (R&D) subsidiaries. Design/methodology/approach In a conceptual paper, this study explores specific institutional facets of the regional environments within a country that are capable of explaining, at least in part, the location choices of multinational corporations' R&D subsidiaries. Findings This study thus explores the more nuanced influences of the institutional environments at a subnational level and develops propositions to explain location choices based on the differences of the institutional environments. Originality/value This study contributes to international business theory by incorporating a location-specific analysis that contrasts to the usual country-level observation on the determinants of firms' location decisions.
Keywords: 650; Innovation; Institutional environment; Location choice; Regional differences